2017
DOI: 10.1186/s12859-017-1859-6
|View full text |Cite
|
Sign up to set email alerts
|

Identify Huntington’s disease associated genes based on restricted Boltzmann machine with RNA-seq data

Abstract: BackgroundPredicting disease-associated genes is helpful for understanding the molecular mechanisms during the disease progression. Since the pathological mechanisms of neurodegenerative diseases are very complex, traditional statistic-based methods are not suitable for identifying key genes related to the disease development. Recent studies have shown that the computational models with deep structure can learn automatically the features of biological data, which is useful for exploring the characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Finally, we compared our results with the existing ML-based method [ 14 ] for identifying HD-contributing genes and checked whether these 66 contributing genes are included in the known HD gene set. Out of the 66 genes, 13 genes are mutually identified in both ML studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we compared our results with the existing ML-based method [ 14 ] for identifying HD-contributing genes and checked whether these 66 contributing genes are included in the known HD gene set. Out of the 66 genes, 13 genes are mutually identified in both ML studies.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the emergence of a wide range of biological data of HD, including genomic profiling and electronic health records, a comprehensive understanding of the mechanism of HD from ML is so far unrealized, majorly due to the lack of needed data density [ 13 ]. For example, a previous ML study on RNA profiling of HD reported 4433 candidate genes from 16 samples [ 14 ], which is a typical high dimension, low sample size (HDLSS) situation, and ML may suffer from overfitting and low convergence. In this study, to harness the knowledge of the HD mechanism from the existing data, we tackled the data density issue by rationally reducing the dimension size, and identified the enriched pathways of HD by ML.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above methods could not effectively distinguish the disease-associated genes from the non-disease-associated genes in the modifier gene set. Possible reasons for this may be that the expression levels of the disease-associated genes did not change significantly during the disease’s progression, or that a large number of gene expression levels had changed during the disease’s progression, thereby making it difficult to identify the disease-associated genes [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Critical proteins exhibiting dramatic structural changes in dynamic protein-protein interactions networks were identified in [80] using a DBN framework; the reconstruction errors and the variabilities across time were analyzed in the biological process. In [81], a DBM framework called stacked RBM was proposed to analyze the RNA-seq data of Huntington disease. In addition, the framework was able to screen the key genes during the Huntington disease development.…”
Section: Review Of Deep Learning Implementation In Health Carementioning
confidence: 99%